A closed-loop supply chain network design for automotive industry in Turkey. (November 2017) - Özceylan, Eren; Demirel, Neslihan; Çetinkaya, Cihan; Demirel, Eray
Highlights: A CLSC network design problem for ELVs is considered. A linear programming model is developed. Maximization of revenue and minimization of cost are aimed. A case study including 998 different facilities is presented. Several CLSC scenarios are discussed. Abstract: Increasing worldwide environmental and social concerns are motivating manufacturers and consumers to implement recycling strategies such as product recovery, waste management or usage of recycled materials. Besides environmental and social concerns, in some countries legislations also force recycling of products such as end-of-life vehicles (ELVs). Automotive manufactures in Turkey are responsible for free take-back of ELVs from consumers to reintegrate used parts into industry according to ELVs regulation by Republic of Turkey Ministry of Environment and Urbanization. Regarding mentioned motivation, in this study a closed-loop supply chain (CLSC) is presented, based on a case study considering the ELVs treatment in Turkey. A linear programming (LP) model is developed to handle the reverse material flows with regard to reintegrate them into forward supply chains. Several CLSC scenarios are discussed to show the performance of the proposed model and its applicability in the automotive industry.